The Role of Students in Developing Democratic Awareness: Implementation Fourth Principle of Pancasila - Anggraeni , Andini Eka; Maulida, Hifzani; Ardana, Zalfaa Pramesty; Mafrucha, Zunatul; Sulistianingsih, Dewi (Indonesian Journal of Pancasila and Global Constitutionalism, 2025)
This research is based on the importance of raising awareness of democracy in the context of the nation and state, particularly regarding the implementation of the values ​​of the fourth principle of Pancasila among college students. The purpose of this study is to evaluate the role of students in strengthening democratic awareness, as reflected in the principle of deliberation and consensus, contained in the fourth principle of Pancasila, within the campus environment. The methodology used involved a literature review using a content analysis approach to several written references on democracy and the role of students. The results indicate that students play a significant role as agents of change who implement democratic values ​​through active participation in student organizations, holding general elections on campus, and political education related to democracy. However, several challenges, such as differing perspectives and low collective awareness, need to be addressed through improved democratic education. The benefits of this research are expected to provide academic and practical guidance for the development of civic education and strengthen the role of students as drivers of a healthy and sustainable democracy in Indonesia.